A segurança e defesa cibernética no Brasil e uma revis\~ao das estratégias dos Estados Unidos, Rússia e Índia para o espaço virtual - Samuel César da Cruz Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Computing, electronics and internet provides the free and fast flow of information across the globe. In a way, modern society depends on these autonomous control systems. However, this technological innovation requires a price to be paid: investment in cyber security of people, data, information and infrastructure. Some countries have already absorbed the issue as a matter of state and institutionalized government structures to take care exclusively of it. This paper presents some relevant points of the International Strategy for Cyberspace of the United States, besides the positioning of Russia and India on the subject. It then presents an overview of the Brazilian situation, from the the National Defense Strategy, a document that introduces the responsibility of protecting Brazilian cyberspace. It shows the arrangement, in the federal government hierarchy, of the various national agencies and organizations responsible for conducting intelligence activities necessary for the national security of Brazil. Finally, it provides an overview of the IT infrastructure existing in Brazil, especially in the federal public administration.
Keywords: O3; O31; O38; 330; cyber security and defense; institutional arrangement; international comparison; USA; Russia; India; Brazil